Solar Absorption air conditioning - Tang, Chung Hieng. (Universiti Malaysia Sarawak, UNIMAS, 2005)
The compression refrigerator system is one of the most conventional cooling systems for both offices and residential usage. However, this system leads to the high - energy consumption and the material it uses i.e. CFC, which believed, could impoverished the layer of ozone. Therefore, a study of a solar powered absorption system could be interesting. This project is aimed to investigate the process of the solar absorption air conditioning with LiBr - H 2 O by simple computer modeling using Matlab for education purpose. The conceptual modeling was done to determine energy, concentration of solution and steam, mass statement of each cycle. In the simulation process, the variation of coefficient of performance solar abs orption air conditioning was determined in different temperature of one component with other components maintains as constant. The relationship between the COPs and temperature of components was analyzed and studied. The exergy study also had been conducte d in this final year project study.